Ozonation of Indigo Carmine Catalyzed with Fe-Pillared Clay. (20th November 2013) - Bernal, Miriam; Romero, Rubí; Roa, Gabriela; Barrera-Díaz, Carlos; Torres-Blancas, Teresa; Natividad, Reyna
Abstract : The ozonation catalyzed by iron-pillared clays was studied. The degradation of dye indigo carmine (IC) was elected as test reaction. Fe-pillared clays were synthesized by employing hydrolyzed FeCl3 solutions and bentonite. The pillared structure was verified by XRD and by XPS the oxidation state of iron in the synthesized material was established to be +2. By atomic absorption the weight percentage of iron was determined to be 16. The reaction was conducted in a laboratory scale up-flow bubble column reactor. From the studied variables the best results were obtained with a particle size of 60 microns, pH = 3, ozone flow of 0.045 L/min, and catalyst concentration of 100 mg/L. IC was completely degraded and degradation rate was found to be double when using Fe-PILCS than with ozone alone. DQO reduction was also significantly higher with catalyzed than with noncatalyzed ozonation.